Unanticipated Difficulty in an Anticipated Difficult Airway in the Neurointervention Suite: A Case Report - Gandhe, Rajashree Uday; Bhave, Chinmaya Pradeep; Kakde, Avinash Sahebarav; Sathe, Kalyani Anand (Journal of Neuroanaesthesiology and Critical Care, 2018)
Airway management of patients with craniofacial vascular malformations poses many challenges. Establishment of a secure airway is a prerequisite for safe anesthetic management of these patients. We report a case of a 45-year-old man presenting with a facial vascular malformation involving the tongue, parapharynx, and extending into the neck, resulting in airway compromise scheduled for endovascular embolization.
Keywords: difficult airway; neurointervention; vascular malformation